Study of serum vitamin d levels and its association with neonatal sepsis among newborns - Dr. Vijay Kumar Gupta; Dr. (Mrs) Mamta Dhaneria (Pediatric Review: International Journal of Pediatric Research, 2020)
Introduction: Vitamin D plays an important role in immune function. It plays an important role in the neonatal period in fetal skeletal growth, prevention of rickets, neonatal sepsis, respiratory tract infections, cardiovascular diseases, diabetes, and other endocrine disorders. It has been found that newborns’ low level of cholecalciferol is closely related to neonatal sepsis. Aims and Objectives: To determine the neonatal plasma cholecalciferol levels and severity of vitamin D deficiency in neonatal sepsis. Material and Methods: This was a prospective, observational study conducted at Neonatal Care Intensive Unit of R. D. Gardi Medical College, Ujjain. The cases included all babies >34 weeks of gestational age having postnatal age of 0-28 days with clinical signs and laboratory findings of neonatal sepsis. Statistical analysis was performed using STATA 10.0. Results: Total 70 newborns with sepsis were included in the study among which n=47 (67%) had deficient (less than 20ng/ml), n=16 (22.86%) had insufficient (between 20-30ng/ml) and n=7 (10.00%) of newborns had sufficient levels of cholecalciferol (more than 30ng/ml). The mean cholecalciferol levels among term were 18.53ng/ml (±4.8) and in preterm is 15.7ng/ml (±2.6) and this finding was statistically significant (p=0.04). The mean cholecalciferol in newborns with culture-positive sepsis was 14.8ng/ml (±6.04) and in culture-negative sepsis was 16.4ng/ml (±5.2) and this finding was statistically significant (p=0.02). Conclusions: More than 65% of newborns were deficient in 25-OH cholecalciferol and the mean 25-OH cholecalciferol levels were lower in preterm than in term newborns and lower in newborns with culture-positive sepsis than in newborns with culture-negative sepsis.